Disability weights for environmental noise-related health states: results of a disability weights measurement study in Europe - Juanita A Haagsma; Periklis Charalampous; Carolien C H M Maas (BMJ Public Health)
Introduction Measurement of the burden of disease using disability-adjusted life years requires disability weights to quantify health losses for non-fatal consequences of disease and injury. We aimed to obtain a set of disability weights for environmental and non-environmental noise-related health states (NOISE) using a nationally representative sample survey among the general population of four European countries; and to compare the resulting NOISE disability weights with those estimated in the Global Burden of Disease 2010 (GBD 2010) and European (EURO) disability weights measurement studies.Methods We administered a web-based survey among a cohort of individuals from Hungary, Italy, Sweden and the Netherlands. It included paired comparison questions on 82 different health states. Each respondent performed 13 paired comparison tasks. We analysed paired comparison responses with probit regression analysis, and regression results were anchored on the disability weight scale between 0 (equivalent to full health) and 1 (equivalent to death).Results In total, 4056 respondents participated in the study. Comparison of the regression results from paired comparison responses for each country-specific dataset with those run on the pooled dataset showed high linear correlations (0.96–0.98, p<0.001). The resulting disability weights ranged from 0.005 for mild impairment of distance vision and mild anaemia to 0.761 for intensive care unit admission. The disability weight for moderate and severe annoyance was 0.006 and 0.011, respectively. Comparison of disability weights showed a higher correlation between EURO and NOISE disability weights (pseudo R-squared=0.955, Pearson correlation=0.954) compared with GBD 2010 and NOISE disability weights (pseudo R-squared=0.893, Pearson correlation=0.946).Conclusions The NOISE disability weights are consistent and highly correlated across the four European countries. The NOISE disability weights set can be used to estimate the burden of disease attributable to noise-related outcomes across Europe.